World mortality 1950-2000: divergence replaces convergence from the late 1980s. - Moser, K; Shkolnikov, V; Leon, D (2005)
OBJECTIVE: We sought to investigate to what extent worldwide improvements in mortality over the past 50 years have been accompanied by convergence in the mortality experience of the world's population. METHODS: We have adopted a novel approach to the objective measurement of global mortality convergence. The global mortality distribution at a point in time is quantified using a dispersion measure of mortality (DMM). Trends in the DMM indicate global mortality convergence and divergence. The analysis uses United Nations data for 1950-2000 for all 152 countries with populations of at least 1 million in 2000 (99.7% of the world's population in 2000). FINDINGS: The DMM for life expectancy at birth declined until the late 1980s but has since increased, signalling a shift from global convergence to divergence in life expectancy at birth. In contrast, the DMM for infant mortality indicates continued convergence since 1950. CONCLUSION: The switch in the late 1980s from the global convergence of life expectancy at birth to divergence indicates that progress in reducing mortality differences between many populations is now more than offset by the scale of reversals in adult mortality in others. Global progress needs to be judged on whether mortality convergence can be re-established and indeed accelerated.